2021
DOI: 10.1590/1413-785220212901231439
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of the Treatment of Clavicle Fractures: Intramedullary Nail × Plate

Abstract: Objective: Studies confirm the benefit of surgical treatment for fixation of displaced midshaft clavicle fractures. Plate fixation and intramedullary nail are the two most used techniques. Our study seeks to compare these two surgical techniques. Methods: This is a retrospective study, conducted by the evaluation of patients treated for displaced midshaft clavicle fracture with intramedullary nail, and plate and screws. Socioeconomic variables were collected, a visual pain scale questionnaire was applied, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Concerning superior locking plates, 23 studies were identified. 1 , 2 , 4 , 9 , 10 , 12 , 13 , 17 , 19 , 20 , 24 , 28 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 63 , 66 , 76 The average patient age from all studies was 37.8 years (range 17-79) with mean length of follow-up of 29.3 months. Five studies reported a Constant-Murley Score (CMS) 14 at 6 months, 1 of these studies did not include a standard error.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning superior locking plates, 23 studies were identified. 1 , 2 , 4 , 9 , 10 , 12 , 13 , 17 , 19 , 20 , 24 , 28 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 63 , 66 , 76 The average patient age from all studies was 37.8 years (range 17-79) with mean length of follow-up of 29.3 months. Five studies reported a Constant-Murley Score (CMS) 14 at 6 months, 1 of these studies did not include a standard error.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies that did report time points did not use the same time points addressed in this review. Finally, several studies used a functional outcome measure that we were not analyzing, 1 , 5 , 12 , 49 , 63 which prevented us from including such studies in the meta-analyses. Despite heterogeneity, the individual study complications and functional outcome scores were pooled.…”
Section: Methodsmentioning
confidence: 99%